2010
DOI: 10.1101/gr.109405.110
|View full text |Cite
|
Sign up to set email alerts
|

CRX ChIP-seq reveals the cis-regulatory architecture of mouse photoreceptors

Abstract: Approximately 98% of mammalian DNA is noncoding, yet we understand relatively little about the function of this enigmatic portion of the genome. The cis-regulatory elements that control gene expression reside in noncoding regions and can be identified by mapping the binding sites of tissue-specific transcription factors. Cone-rod homeobox (CRX) is a key transcription factor in photoreceptor differentiation and survival, but its in vivo targets are largely unknown. Here, we used chromatin immunoprecipitation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
310
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(328 citation statements)
references
References 76 publications
18
310
0
Order By: Relevance
“…Using ChIP-qPCR, we show that three transcription factors, CRX, NRL, and NR2E3, differentially bind to rod vs. cone opsin genes in a subtype-specific manner. CRX preferentially binds to each opsin in the respective photoreceptor subtype expressing it, in agreement with CRX ChIP-seq results (33) and consistent with CRX's role as a trans-activator. In contrast to the discrete binding sites detected by ChIP-seq, ChIPqPCR revealed that CRX is bound along the entire length of each active opsin locus.…”
Section: Discussionsupporting
confidence: 72%
“…Using ChIP-qPCR, we show that three transcription factors, CRX, NRL, and NR2E3, differentially bind to rod vs. cone opsin genes in a subtype-specific manner. CRX preferentially binds to each opsin in the respective photoreceptor subtype expressing it, in agreement with CRX ChIP-seq results (33) and consistent with CRX's role as a trans-activator. In contrast to the discrete binding sites detected by ChIP-seq, ChIPqPCR revealed that CRX is bound along the entire length of each active opsin locus.…”
Section: Discussionsupporting
confidence: 72%
“…2, 3), provided preliminary evidence that it may represent a putative enhancer element, similar to what has been previously reported for other conserved sequences (Pennacchio et al 2006). Moreover, a previous finding of a binding site for CRX validated by ChIP-seq, within the Vax2os1 conserved region, seems to further support this hypothesis (Corbo et al 2010). CRX (Cone-Rod Homeobox) is a transcription factor known to play an important role in cone and rod maturation by regulating the expression of a number of photoreceptorspecific genes (Chen et al 1997;Freund et al 1997;Furukawa et al 1997).…”
Section: Discussionsupporting
confidence: 72%
“…30 Indeed, two cis-regulatory elements bound by CRX are located in the GRID2 region, and one of them is removed by the homozygous deletion in our proband (Supplementary Figure S4 online). Although we cannot exclude RD and concordant ERG changes in the GRID2 deletion mutants based on the clinical data reported by Utine et al, 4 Hills et al, 5 and Maier et al, 6 the absence of a retinal phenotype in these patients might be explained by intact cis-regulatory elements bound by CRX on at least one of the two alleles.…”
Section: Discussionmentioning
confidence: 99%